Design of Solar Panel Based Powerbank with Control System BMS (Battery Management System) - Sholeha, Dewi; Sasmito, Yoga Himawan (Journal of Renewable Energy, Electrical, and Computer Engineering, 2025)
Electrical energy is the main energy for humans. Electrical energy has a very important role in the development of modern technology in all sectors of households and industries. Electrical energy must be sustainable for human survival. Therefore, the problem of saving electrical power needs to be raised in research. This study aims to design a solar panel-based power bank to meet household electricity needs such as fans. This is done to reduce the use of electricity costs sourced from PLN. The study's results showed that by using 1 sheet of GH Solar 50 Wp solar panel, 4 units of LI-P0 12 Volt 22 AH batteries using a series circuit and an inverter. Each installed component meets the specifications, so this PLTS system can turn on 1 fan unit with a load power of 42.0 Watts. Furthermore, for charging HP of 8 watts and Laptop of 40.3 watts for 2 hours 45 minutes for 1 day.